PENINGKATAN KEMAMPUAN LOGIKA BERPIKIR ANAK MELALUI PENGENALAN PLATFORM CODING BLOCK SCRATCH - Ashlihah Ashlihah; Moh. Anshori Aris Widya; Melfika Sheylawatin; Ivan Kafi Pradana; Arif Syaifudin; Rismah Bilqis Maulidiyah (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2026)
The Community Service Program in Sumobito Village, Sumobito District, Jombang Regency, aimed to improve children's logical thinking skills through the introduction of the Scratch coding platform. The challenges faced were the limited use of technology in learning and students' lack of programming experience. The activities involved lectures, demonstrations, and hands-on practice, enabling students to create animations, educational games, and learn about simple artificial intelligence. As a result, students were more motivated to learn, able to think logically, and create interactive learning media. The output of this activity was a Scratch guide module that can be used continuously by teachers and students. Keywords: Scratch, logical thinking, coding, interactive learning.